Respuesta :

In this exercise, we want to know the x-intercepts of each item. To find the x-intercepts, set y = 0 as indicated in each item and solve for x. So:

1. Answer:

B. x=-1; x=-1.75

Step by step explanation:

we have the equation:

[tex]4x^2+11x+7=0[/tex]

We can say that this equation comes from the function [tex]f(x)=4x^2+11x+7[/tex] so we have set [tex]y=0[/tex] to find the x-intercepts. By using the quadratic formula we have:

[tex]x=\frac{-b \pm \sqrt{b^2-4ac}}{2a} \\ \\ where: \\ \\ a=4, \ b=11, \ c=7 \\ \\ x=\frac{-11 \pm \sqrt{11^2-4(4)(7)}}{2(4)} \\ \\ x=\frac{-11 \pm \sqrt{121-112}}{8} \\ \\ \boxed{x_{1}=-1 \ and \ x_{2}=-1.75}[/tex]

2. Answer:

B. x=-1; x=-1.75

Step by step explanation:

we have the equation:

[tex]3x^2-4x+1=0[/tex]

We can establish a function [tex]g(x)=3x^2-4x+1[/tex] and say that we want to find the x-intercepts of this function by setting y = 0. Therefore, by using the quadratic formula we have:

[tex]a=3, \ b=-4, \ c=1 \\ \\ x=\frac{-(-4) \pm \sqrt{(-4)^2-4(3)(1)}}{2(3)} \\ \\ x=\frac{4 \pm \sqrt{16-12}}{6} \\ \\ \boxed{x_{1}=1 \ and \ x_{2}=\frac{1}{3}}[/tex]

3. Answer:

H. No Solution

Step by step explanation:

we have the equation:

[tex]3x^2-4x+2=0[/tex]

We can establish a function [tex]h(x)=3x^2-4x+2[/tex] and say that we want to find the x-intercepts of this function by setting y = 0. Therefore, by using the quadratic formula we have:

[tex]a=3, \ b=-4, \ c=2 \\ \\ x=\frac{-(-4) \pm \sqrt{(-4)^2-4(3)(2)}}{2(3)} \\ \\ x=\frac{4 \pm \sqrt{16-24}}{6}[/tex]

Since 16 - 24 = -8, that is, a number less than zero which is within a square root, we say that the equation [tex]3x^2-4x+2=0[/tex] has no any real solution.

4. Answer:

E. x=1

Step by step explanation:

we have the equation:

[tex]x^2-2x+1=0[/tex]

We can establish a function [tex]c(x)=x^2-2x+1[/tex]. By setting y = 0 we'll find the x-intercepts. Let's solve this problem using other method. You can find some binomial products having a special form. So it's easier to find a solution by using distributive. The form of this polynomial is a Square of a Binomial in the form:

[tex](x-1)^2=0 \\ \\ Because: \\ \\ (x-1)^2=(x-1)(x-1)=x^2-x-x+1= x^2-2x+1[/tex]

Therefore, the value that satisfies this equation is [tex]\boxed{x=1}[/tex]

5. Answer:

K. x = -1

Step by step explanation:

we have the equation:

[tex]x^2+2x+1=0[/tex]

We can establish a function [tex]a(x)=x^2+2x+1[/tex]. By setting y = 0 we'll find the x-intercepts. We are going to solve this problem by using the previous method. The form of this Square of a Binomial is:

[tex](x+1)^2=0 \\ \\ Because: \\ \\ (x+1)^2=(x+1)(x+1)=x^2+x+x+1= x^2+2x+1[/tex]

Therefore, the value that satisfies this equation is [tex]\boxed{x=-1}[/tex]

6. Answer:

N) x = 1/2

Step by step explanation:

we have the equation:

[tex]4x^2-4x+1=0[/tex]

We can establish a function [tex]b(x)=4x^2-4x+1[/tex] and say that we want to find the x-intercepts of this function by setting y = 0. Here we will use the quadratic formula, so:

[tex]a=4, \ b=-4, \ c=1 \\ \\ x=\frac{-(-4) \pm \sqrt{(-4)^2-4(4)(1)}}{2(4)} \\ \\ x=\frac{4 \pm \sqrt{16-16}}{8} \\ \\ \boxed{x=\frac{1}{2}}[/tex]

So we have just one solution.

7. Answer:

M) x = -1/2

Step by step explanation:

we have the equation:

[tex]4x^2+4x+1=0[/tex]

We can establish a function [tex]b(x)=4x^2+4x+1[/tex] and say that we want to find the x-intercepts of this function by setting y = 0. As in the previous exercise, we will use the quadratic formula, so:

[tex]a=4, \ b=4, \ c=1 \\ \\ x=\frac{-4 \pm \sqrt{(4)^2-4(4)(1)}}{2(4)} \\ \\ x=\frac{-4 \pm \sqrt{16-16}}{8} \\ \\ \boxed{x=-\frac{1}{2}}[/tex]

So we have just one solution.

8. Answer:

D) x = -1.45; x=1.25

Step by step explanation:

we have the equation:

[tex]5x^2+x-9=0[/tex]

We can establish a function [tex]D(x)=5x^2+x-9[/tex] and say that we want to find the x-intercepts of this function by setting y = 0. By using the quadratic formula we can solve this problem, so:

[tex]a=5, \ b=1, \ c=-9 \\ \\ x=\frac{-1 \pm \sqrt{(1)^2-4(5)(-9)}}{2(5)} \\ \\ x=\frac{-1 \pm \sqrt{1+180}}{10} \\ \\ \boxed{x_{1}=-1.45 \ and \ x_{2}=1.25}[/tex]

9. Answer:

J) x = 4; x=-3

Step by step explanation:

we have the equation:

[tex]-x^2+x+12=0[/tex]

We can establish a function [tex]k(x)=-(x^2-x-12)[/tex] and say that we want to find the x-intercepts of this function by setting y = 0. In this exercise we'll use other method. Since this is a non-perfect square trinomial, we know that:

[tex](x+a)(x+b)=x^2+(a+b)x+ab[/tex]

So let's find two numbers such that the sum is -1 and the product is -12. Those numbers are -4 and 3, thus:

[tex]-(x-4)(x+3)=-x^2+x+12=0[/tex]

Therefore, our solutions are:

[tex]x=4 \ and \ x=-3[/tex]

________________

THE OTHER SOLUTIONS HAVE BEEN ATTACHED BELOW

Ver imagen danielmaduroh

Answer:

Do you need the workings for each of the questions?

Step-by-step explanation:

ACCESS MORE